Ion Beam Analysis applied to laser-generated plasmas. (14th April 2016) - Cutroneo, M.; Macková, A.; Havranek, V.; Malinsky, P.; Torrisi, L.; Kormunda, M.; Barchuk, M.; Ullschmied, J.; Dudzak, R.
Abstract: This paper presents the research activity on Ion Beam Analysis methods performed at Tandetron Laboratory (LT) of the Institute of Nuclear Physics AS CR, Rez, Czech Republic. Recently, many groups are paying attention to implantation by laser generated plasma. This process allows to insert a controllable amount of energetic ions into the surface layers of different materials modifying the physical and chemical properties of the surface material. Different substrates are implanted by accelerated ions from plasma through terawatt iodine laser, at nominal intensity of 10 15 W/cm 2, at the PALS Research Infrastructure AS CR, in the Czech Republic. This regime of the laser matter interaction generates, multi-MeV proton beams, and multi-charged ions that are tightly confined in time (hundreds ps) and space (source radius of a few microns). These ion beams have a much lower transverse temperature, a much shorter duration and a much higher current than those obtainable from conventional accelerators. The implementation of protons and ions acceleration driven by ultra-short high intensity lasers is exhibited by adopting suitable irradiation conditions as well as tailored targets. An overview of implanted targets and their morphological and structural characterizations is presented and discussed.